The Excess Burden of Taxation and Why it (Approximately) Quadruples When the Tax Rate Doubles - John Creedy (New Zealand Government, The Treasury, 2003)
The 'excess burden' of taxation represents an efficiency loss which must be compared with any perceived gains arising either from income redistribution or the non-transfer expenditure carried out by the government. An important property is that, under certain assumptions, it increases disproportionately with the tax rate. This result provides the basis of a general presumption in favour of a broad-based and low tax rate system: any exemptions which reduce the tax base inevitably raise the tax rate required to obtain anunchanged amount of total tax revenue. The aims of this paper are to provide a nontechnical explanation of the concepts of welfare change and excess burden used in the public finance literature, and to demonstrate the result that an approximation to thisburden depends on the square of the tax rate.
Keywords: H21; H30; D60; 330; Taxation; excess burden; equivalent variation; compensating variation